Människors benägenhet till utrymning vid alkoholpåverkan - Björkqvist,Malin; Franzén Broholm,Agnes (LUTVDG/TVBB, 2018)
The aim of this thesis is to investigate how alcohol affects people’s tendency to evacuate. There are many examples of fires in nightclubs where people have been drinking alcohol, and where the number of fatalities became high. To be able to study the effect that alcohol can have on evacuation, laboratory experiments were performed. The participants were divided in three test groups: one non-alcohol group and two groups where the participants were given alcohol. During the experiments, one participant at a time was playing a computer game alone in a room. After five minutes an unannounced fire alarm was set of. The participants behavior was studied using EyeTrack, glasses that register what the participants was looking at. In the room there was also a video camera. Of the 60 participants, 15 evacuated. After the test, the researchers asked some questions about how the participants had experienced the experiment. The analysis of the answers shows that the non-alcohol group was more likely to feel stress and fear compared to the other groups. When talking to the participants, a difference in the arguments about why they did or did not evacuate could also be found. The people in the non-alcohol group tended to be more aware of their decisions and had a deeper analysis of why they acted like they did.
Keywords: alkohol; utrymning; kontrollerade försök; bränder i nattklubbar; säkerhet; EyeTrack; etiska aspekter